1986
DOI: 10.1017/s0043174500067436
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Translocation of Herbicides with Lipid Compounds

Abstract: Absorption and translocation of14C following14C-fluazifop {(±)-2-[4-[[5-(trifluoromethyl)-2-pyridinyl] oxy] phenoxy] propanoic acid} butyl ester and14C-sethoxydim {2-[1-(ethoxyimino)butyl]-5-[2-(ethylthio)propyl]-3-hydroxy-2-cyclohexen-1-one} application to oats (Avena sativaL. ‘Lyon’) was greater when the herbicides were applied with oleic acid, linoleic acid, or fatty acid methyl esters compared to various triglycerides. The methyl esters of stearic, oleic, linoleic, and linolenic acids enhanced14C absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 2 publications
2
18
0
Order By: Relevance
“…Thus absorption, penetration and translocation of several herbicides were enhanced with adjuvants (Nalewaja et al 1986;Foy 1996). Formulation of a microbial product results in a product that has low cost, long shelf life, ease of application and efficacy.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Thus absorption, penetration and translocation of several herbicides were enhanced with adjuvants (Nalewaja et al 1986;Foy 1996). Formulation of a microbial product results in a product that has low cost, long shelf life, ease of application and efficacy.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Work by Nalewaja's group (Nalewaja 1986;Nalewaja et al 1990) has shown the biological activation potential of oils and their derivatives with a selection of herbicides. The activity, if not penetration, potential of such formulations can be great.…”
Section: Effect Off Ormulation On Foliar Penetrationmentioning
confidence: 99%
“…The slide was tilted after Manthey and Nalewaja 1992) various times and the wax was then firmly wiped perpendicular to the oil drainage. The herbicides studied were fluazifop-butyl and sethoxydim on oats (Nalewaja et al 1986), diclofop-methyl on maize (Urvoy and Gauvrit 1991), and quizalofop-ethyl on oats and S. glauca (Manthey et al 1992a). A comparison between petroleum oil, sunflower oil, and its methyl ester is shown in Fig.…”
Section: Effect On Waxmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several reports have shown that seed oil additives can increase the efficacy of post-emergence herWcides, particularly graminicides De Ruiter etal., 1987;Parmentier, 1987;Gillespie et al, 1988;McWhorter & Barrentine, 1988;Schott et al, 1990Schott et al, , 1991. Methylated esters obtained from seed oils usually perform better than the parent oil and are comparable to petroleum oils, in some instances better Nalewaja et al, 1986;Manthey et al, 1989;Schott et al, 1990Schott et al, , 1991.…”
Section: Introductionmentioning
confidence: 99%